Fluorescent Ligand-Based Discovery of Small-Molecule Sulfonamide Agonists for GPR120 - Ma, Siyue; Li, Zhenzhen; Yang, Yueli; Zhang, Ling; Li, Minyong; Du, Lupei (Frontiers in Chemistry, 2022)
As a critical member of G protein-coupled receptors (GPCRs), G protein-coupled receptor 120 (GPR120) is a potential target for many physiological diseases, such as type 2 diabetes mellitus, inflammation, and obesity. Considering that small-molecule fluorescent ligands have the advantages of visualization, high sensitivity and selectivity, we initially undertook an effort to develop a series of fluorescent ligands to track GPR120 and establish a method to screen GPR120 agonists. The representative fluorescent ligand N1 possesses suitable optical property, equitable biological activity, and high fluorescence imaging feasibility, therefore, based on compound N1, we subsequently founded a bioluminescence resonance energy transfer (BRET) competition binding assay to screen three series of sulfonamide GPR120 agonists we developed herein. The activity evaluation results revealed that compound D5 was a potent GPR120 agonist with high activity and selectivity. Moreover, compound D5 exhibited a significant glucose-lowering effect in db/db mice, which indicates its potential application in the treatment of type 2 diabetes mellitus in vivo. It is anticipated that our fluorescent ligand-based method is a useful toolbox and will find broad applications in the discovery of small-molecule agonists for GPR120.